De novo 911 Kb interstitial deletion on chromosome 1q43 in a boy with mental retardation and short stature. - Perrone, M D; Rocca, M S; Bruno, I; Faletra, F; Pecile, V; Gasparini, P (Eur J Med Genet, 2012)
Patients with distal deletions of chromosome 1q have a recognizable syndrome that includes microcephaly, hypoplasia or agenesis of the corpus callosum, and psychomotor retardation. Although these symptoms have been attributed to deletions of 1q42-1q44, the minimal chromosomal region involved has not yet defined. In this report, we describe a 7 years old male with mental retardation, cryptorchid testes, short stature and alopecia carrying only an interstitial de novo deletion of 911 Kb in the 1q43 region (239,597,095-240,508,817) encompassing three genes CHRM3, RPS7P5 and FMN2.
Keywords: Child; Chromosomes, Human, Pair 1; Dwarfism; Humans; Intellectual Disability; Male; Sequence Deletion